PELATIHAN MANAJEMEN DASAR KEAMANAN DATA INTERNET UNTUK MENINGKATKAN LITERASI PADA SISWA SMK ALMANAAR - Nugroho, Catur; Sahara, Riad; Saputra, Muhammad Ikhwani; Hassolthine, Cian Ramadhona (JAMAIKA: JURNAL ABDI MASYARAKAT, 2025)
The rapid development of information and computer technology has become a necessity for many users. This increases the risk of information security issues such as hacking, data theft, and malware attacks, which can threaten operational continuity and information privacy. Al-Manar Islamic Vocational School has a major in Information Technology, one of which is Network Security. The introduction to cybersecurity is aimed at 12th grade students majoring in TKJ because the school needs to provide additional education and socialization for students in the use of technology in order to improve their literacy in the use of internet data and cybersecurity risks. It is important to equip students with this knowledge because cybersecurity is a priority of the TKJ Program so that students can increase their awareness of latent risks and adopt appropriate preventive measures against cyber attacks. The activity began with the submission of a proposal, a review of the location, and the implementation of the activity through presentations, discussions, and evaluations. This activity involved 17 participants and lasted for 1.5 hours. The students enthusiastically participated in the theoretical introduction through active participation, lectures, and discussions, with a theoretical introduction to the basic material of computer networks and basic internet network security. From the feedback provided by filling out the Google form link related to the discussion of the material, it can be seen that the material was presented well and could be understood as a whole. In the question and answer session, nearly 89% of the participants responded that the presenter provided clear explanations during the activity and received positive.